ANALISIS ISI DAN STRUKTUR LAPORAN TINDAKAN OKUPASI TERAPI DI POLIKLINIK REHABILITASI MEDIK UNIT OKUPASI TERAPI RSUD DR MOEWARDI SURAKARTA - SUMARYANTO, EKO, Prof., dr. Bhisma Murti, M.PH., M.Sc., Ph.D, Dwi Astuti, S.Pd., M.Kes (2011)
Occupational therapy health record contains diverse principal information related to client's identity, therapy progress, and performance achievement. The research itself aims to identify and to explore any information associated with content and structure of the occupational therapy health record which utilize by the hospital. The research is attempt to frame out and to recognize the completeness of content along with structure's component. The study was qualitative-descriptive. Conducted during period of April and May 2011 at Occupational Therapy Unit of Medical Rehabilitation Clinic of dr. Moewardi General Hospital in Surakarta. The thematic analysis or grounded theory is used as a tool of data analysis trough application of data source and data collecting methods triangulation. The triangulation are either used as way of data collection and also ensure the research validity. Based on completeness of content and structure, the research result in conclusion of imperfect content and structure component which imply necessity for further development in occupational therapy health record.